Fabrication of Fe3O4/ZIF‐67 composite for removal of direct blue 80 from water. (23rd November 2019) - Li, Mingyan; Gao, Dasheng; Cui, Shuang; Shi, Yan; Liu, Ningning
Abstract: Fe3 O4 /ZIF‐67 composite was successfully fabricated by a facile method and used as adsorbent to remove direct blue 80 (DB80, azo dye) from water. Characterizations of Fe3 O4 /ZIF‐67 composite were performed by scanning electron microscopy (SEM), powder X‐ray diffraction (PXRD), X‐ray photoelectron spectroscopy (XPS), N2 adsorption/desorption isotherms, Fourier transform infrared spectroscopy (FTIR), and magnetic property analysis. As an adsorbent, the factors (such as adsorbent dose, pH, initial concentration, contact time, and temperature) affecting the adsorption performance of adsorbent were investigated. The optimal adsorption condition is 5 mg of Fe3 O4 /ZIF‐67 composite in 8 ml of DB80 solution (70 mg/L) for 60 min at 318 K, and the pH value has little effect on the adsorption performance. The adsorption isotherm, kinetics, and thermodynamics of DB80 adsorbed on the Fe3 O4 /ZIF‐67 composite were also studied. The experimental results revealed that the experimental data followed the Langmuir model and the adsorption behavior could be well explained by pseudo‐second‐order kinetic model. Thermodynamic analysis indicated that the adsorption was a spontaneous and endothermic process. Furthermore, the mechanism of DB80 adsorbed on the Fe3 O4 /ZIF‐67 composite was proposed. The occurrence of adsorption might be caused by the π‐π stacking interaction between Fe3 O4 /ZIF‐67 composite and DB80. Practitioner points: Fe3 O4 /ZIF‐67 composite was successfully fabricated via a facile method. Fe3 O4 /ZIF‐67 composite was used to the adsorptive removal of direct blue 80 (azo dye). The kinetic characteristics and thermodynamic parameters were analyzed. The adsorption behavior might be ascribed to the π‐π stacking interaction between Fe3 O4 /ZIF‐67 composite and DB80. Abstract : Fe3 O4 /ZIF‐67 composite was successfully fabricated by a facile method, and it was used as adsorbent to remove DB80 (azo‐dye) from water. The adsorption behavior was studied and the mechanism was also proposed.